Myasthenia Gravis with Thymoma Complication: Dilemmas and Prospective Anesthesiology Approach - Jaya, Pelinggo; Ananda, Pratama; Anggraeni, Novita (Jurnal Ilmu Kedokteran, 2025)
Myasthenia gravis (MG) is an autoimmune disease affecting the postsynaptic neuromuscular junction. Myasthenia Gravis occurs in 1:7500 individuals, mostly female and or Asian. Myasthenia gravis can later be complicated with thymoma, and by several indications might need an operative approach. The need for thymectomy while there is a preexisting neuromuscular anomaly in Myasthenia gravis becomes a dilemma when choosing the right anesthetic regimens. This case report aims to discuss findings and offer a possible anesthetic approach that can be considered for cases of Myasthenia gravis with thymoma complications. We received a referred female patient with main complaints of dyspnoea, which was suspected as lung cancer. After further investigation, we found that the patient has previously been diagnosed with Myasthenia gravis, but did not follow through with her treatment plan. We performed a CT scan and confirmed a suspected thymoma as a complication of her Myasthenia gravis. Tymectomy was performed afterwards under general anesthesia. Post-operative extubation was successful, and maintenance of Myasthenia gravis treatment was followed by a neurologist. MG with thymoma is a rare finding in our hospital. Myasthenia gravis causes neurologic anomalies in which patients require special consideration on choosing a proper anesthesia regimen, as general anesthesia and muscle relaxants can worsen respiratory depression. Developing A proper scoring and suitable management plan will enhance the outcome and quality of life. Currently, there are several known anesthetic and supportive medicine approaches to thymectomy in Myasthenia gravis patients, including alternative regimens with similar efficacy.